Bankruptcy Prediction Using The Altman Z-Score Modification Model in India: A Case Study of Bharti Airtel Limited - Aradhana Sorout; Netra Pal Singh (Southeast Asian Business Review, 2025)
Indian telecom sector is facing intense competition since Reliance Jio has entered the telecom market. Furthermore, the COVID-19 pandemic has further strained the sector. Considering these, evaluating a company's financial health is of paramount importance. In spite of various methods available for determining financial stability, Altman's Z-score modification model has been considered a better tool to forecast the possibilities of bankruptcy and determine financial viability of a company. Therefore, this model has been adopted to track Bharti Airtel’s financial health in light of the aforementioned perspective. The purpose of the study is two-fold. Firstly, it focusses on evaluating the financial standing of Bharti Airtel limited & predicting bankruptcy using Altman's Z-score modification model. Secondly, it evaluates the financial standing of Bharti Airtel in context of seven research hypotheses on the performance of the Z’’-Score Model. The exploratory study is based on secondary data acquired from published sources for a period of ten years (2013 to 2022). The analysis on the basis of Altman's Z-score modification model showed that the financial position of Bharti Airtel weakened as the financial scores moved from grey zone to distress zone towards the end of the study period. But as per the other financial parameters considered in the study, the company is financially stable as the net worth is positive, revenue and market capitalization are also increasing, which is contradictory. Thus, the study highlights the need of re-evaluation of the Z’’-Score model and revising the estimation of coefficients in the model to make it viable in the present-day context for the service industry.